Evaluación de tiempos y costos en procesos constructivos con estructuras metálicas empleando metodología BIM: caso PRONACA Quevedo - Acebo Saltos, Juseph Antonio (2025)
This thesis evaluates the impact of the Building Information Modeling (BIM ) methodology on optimizing time and costs during the construction processes of steel structures at the PRONACA Quevedo industrial plant. A study was conducted comparing conventional project design and development tactics with the use of digital 3D models, well-structured schedules, and logistics management tools. The results show that the use of software such as Autodesk Revit, Trimble Connect, and Microsoft Project clearly improves tracking, reduces waste, and optimizes communication between technical teams. Comparing both working methods revealed significant improvements in both operational efficiency and overhead reduction. This study defines a technical benchmark for implementing BIM in construction projects within the Ecuadorian context.